Thirsting for solutions: Unpacking inadequate water provision in rural communities - Sinazo Sixolisiwe Tshona; Sithenkosi Lungisa; Luluto Mgweba (Africa’s Public Service Delivery & Performance Review)
Background: In South Africa, access to water is not equally spread across the population. As a result, 19% of those living in rural areas lack access to a dependable water source and 33% lack basic sanitation services.